1998
DOI: 10.1021/la980648d
|View full text |Cite
|
Sign up to set email alerts
|

Scanning Force Microscopy Images of Cytochrome c Oxidase Immobilized in an Electrode-Supported Lipid Bilayer Membrane

Abstract: Scanning force microscopic images of cytochrome c oxidase immobilized within an electrode-supported lipid bilayer membrane are reported. These images represent the first direct evidence that the microscopic architecture of this important model system effectively mimics the microstructure proposed for the inner mitochondrial membrane. The images reveal (1) that the oxidase is present as monomers and small aggregates within the supported membrane and (2) that the oxidase constitutes ∼20% of the lipid bilayer mem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 30 publications
1
20
0
Order By: Relevance
“…Recently, direct heterogeneous electron transfer reactions between enzymes and electrodes have also been reported. Direct electron transfer reactions on electrodes were achieved for heme-containing enzymes such as cytochrome oxidases (Cullison et al, 1994;Burgess et al, 1998), cellobiose dehydrogenase (Gorton et al, 1999;Lindgren et al, 2001;Stoica et al, 2005Stoica et al, , 2006Harreither et al, 2007), theophylline oxidase (Christenson et al, 2004), alcohol dehydrogenase (Gorton et al, 1999;Ikeda et al, 1993;Ramanavicius et al, 1999;Razumiene et al, 2001), sulfite oxidase (Ferapontova et al, 2003) and peroxidase (Gorton et al, 1999;Ferapontova et al, 2001;Andreu et al, 2007), as well as for multicopper enzymes such as laccase (Gorton et al, 1999;Shleev et al, 2005b;Gupta et al, 2004;Pita et al, 2006), ascorbate oxidase (Gorton et al, 1999 Shleev et al, 2005b), bilirubin oxidase (Shleev et al, 2004(Shleev et al, , 2005aTsujimura et al, 2004Tsujimura et al, , 2005Zheng et al, 2006;Tominaga et al, 2006), ceruloplasmin (Shleev et al, 2005b) and Cu efflux oxidase (Miura et al, 2007). It was also reported that the direct electron transfer reactions of glucose oxidase at highly oriented pyrolytic graphite and at carbon nanotubes (Patolsky et al, 2004;Gong et al, 2005;Wang, 2005;Gooding, 2005;Ivnitski et al, 2006;…”
Section: Introductionmentioning
confidence: 99%
“…Recently, direct heterogeneous electron transfer reactions between enzymes and electrodes have also been reported. Direct electron transfer reactions on electrodes were achieved for heme-containing enzymes such as cytochrome oxidases (Cullison et al, 1994;Burgess et al, 1998), cellobiose dehydrogenase (Gorton et al, 1999;Lindgren et al, 2001;Stoica et al, 2005Stoica et al, , 2006Harreither et al, 2007), theophylline oxidase (Christenson et al, 2004), alcohol dehydrogenase (Gorton et al, 1999;Ikeda et al, 1993;Ramanavicius et al, 1999;Razumiene et al, 2001), sulfite oxidase (Ferapontova et al, 2003) and peroxidase (Gorton et al, 1999;Ferapontova et al, 2001;Andreu et al, 2007), as well as for multicopper enzymes such as laccase (Gorton et al, 1999;Shleev et al, 2005b;Gupta et al, 2004;Pita et al, 2006), ascorbate oxidase (Gorton et al, 1999 Shleev et al, 2005b), bilirubin oxidase (Shleev et al, 2004(Shleev et al, , 2005aTsujimura et al, 2004Tsujimura et al, , 2005Zheng et al, 2006;Tominaga et al, 2006), ceruloplasmin (Shleev et al, 2005b) and Cu efflux oxidase (Miura et al, 2007). It was also reported that the direct electron transfer reactions of glucose oxidase at highly oriented pyrolytic graphite and at carbon nanotubes (Patolsky et al, 2004;Gong et al, 2005;Wang, 2005;Gooding, 2005;Ivnitski et al, 2006;…”
Section: Introductionmentioning
confidence: 99%
“…From the phase contrast tapping mode atomic force microscopy data reported previously by this group [35], the surface coverage of CcO on the modified electrode was estimated to be approximately 20%. The diameter of the beef CcO is approximately 80 Å based on its crystal structure [58,59], which yields 8.0 · 10 10 CcO molecules on the surface of the modified electrode (geometric area of 0.2 cm 2 ).…”
Section: Resultsmentioning
confidence: 78%
“…Phase contrast tapping-mode scanning force microscopy (TM-SFM) has confirmed that the electrode architecture mimics the native membrane structure of the oxidase [35], i.e., with the large hydrophilic portion of the enzyme protruding from the bilayer as illustrated in cartoon-fashion in (Fig. 1).…”
Section: Introductionmentioning
confidence: 82%
“…Biological and synthetic lipid membranes have also been used as potential materials [7]. The electrochemical behavior of proteins and enzymes in lipid films has been studied previously [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25]. The quasi-reversible electron transfer reactions of myoglobin embedded in cast films of lipids, cationic and anionic type lipids, and biological and synthetic lipids, on a graphite electrode surface have been examined [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%